Comparing self-reported incidental catch among fishermen targeting Pacific halibut and a fishery independent survey. (February 2019) - Figus, Elizabeth; Criddle, Keith R.
Abstract: This paper compares observations of commercial fishermen with a fishery-independent survey, and explores putative relationships between characteristics of fishing operations and incidental catch in the Pacific halibut fishery in Southeast Alaska. Results from a multiple factor analysis demonstrate statistically significant relationships between fishing characteristics and the incidental catch of various species. Results from a proportional odds logistic regression model indicate the presence of a strong unavoidable component of incidental catch in the halibut fishery. Consequently, patterns of incidental catch in this fishery generally paralleled patterns of incidental catch in a fishery-independent stock assessment survey that uses similar gear. This suggests that increased onboard monitoring of this fleet by cameras or human observers is unlikely to reveal broad trends in incidental catch that are not already apparent in the fishery-independent stock assessment survey. Nevertheless, weaker statistically significant relationships in the model indicate that incidental catch may be influenced by observable and controllable characteristics of fishing operations (e.g., fishing grounds, season, vessel length, gear configuration). This suggests a proportional odds model like the one presented in this paper could be used to generate operation-specific estimates of incidental catch by species from incidental catches observed in fishery-independent surveys based on known characteristics of fishing operations.